Increasing Autochthonous Production in Inland Waters as a Contributor to the Missing Carbon Sink - Liu, Zaihua; Yan, Hao; Zeng, Sibo (Frontiers in Earth Science, 2021)
Accounting for the residual land sink (or missing carbon sink) has become a major budget focus for global carbon cycle modelers. If we are not able to account for the past and current sources and sinks, we cannot make accurate predictions about future storage of fossil fuel combustion emissions of carbon in the terrestrial biosphere. Here, we show that the autochthonous production (AP) in inland waters appears to have been strengthening in response to changes in climate and land use, as evidenced by decreasing CO2 emissions from and increasing dissolved organic carbon storage and/or organic carbon burial in inland waters during recent decades. The increasing AP may be due chiefly to increasing aquatic photosynthesis caused by global warming and intensifying human activities. We estimate that the missing carbon sink associated with the strengthening AP in inland waters may range from 0.38 Gt C yr-1 to 1.8 Gt C yr-1 with large uncertainties. Our study stresses the potential role that AP may play in the further evolution of the global carbon cycle. Quantitative estimates of future freshwater AP effects on the carbon cycle may also help to guide the action needed to reduce carbon emissions, and increase carbon sinks in terrestrial aquatic ecosystems.